Evaluation of saline water intrusion along the coastal aquifers of Vadakara, Kerala, South India, using hydro geochemistry and GIS - Megha, S B; Arun, P R; Brijesh, V K (Brawijaya University, 2025)
The hydrogeochemical characteristics and evaluation of saline water intrusion of shallow groundwater in the coastal aquifers of Vadakara have been investigated using geochemical analysis and spatial interpolation techniques. Major ion analysis of groundwater samples was employed to identify saltwater intrusion status. The major ions dissolved in water are Ca, Mg, Na, K, Cl, HCO3, and SO4. Groundwater zones in coastal areas have to be delineated in terms of quality. To identify the origin of saline groundwater in the coastal reaches of Vadakara Taluk, Kozhikode district, Kerala, six different major ionic ratios viz. Na/Cl, (Ca+Mg)/CI, K/Cl, SO4/Cl, Na/Ca, and Ca/SO4 and Base Exchange Index (BEX) were computed from physio-chemical analysis of open wells in the study area. Groundwater aquifers, which have a direct connection to tide-influenced river stretches and the sea, are more susceptible to salinization due to seawater intrusion, according to the spatial representation of the ionic ratios.